2017
DOI: 10.7717/peerj.4001
|View full text |Cite
|
Sign up to set email alerts
|

Sodium salt medium-chain fatty acids andBacillus-based probiotic strategies to improve growth and intestinal health of gilthead sea bream (Sparus aurata)

Abstract: BackgroundThe increased demand for fish protein has led to the intensification of aquaculture practices which are hampered by nutritional and health factors affecting growth performance. To solve these problems, antibiotics have been used for many years in the prevention, control and treatment against disease as well as growth promoters to improve animal performance. Nowadays, the use of antibiotics in the European Union and other countries has been completely or partially banned as a result of the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 72 publications
10
37
0
Order By: Relevance
“…This diversity is now starting to be elucidated, and microarray gene expression profiling of European sea bass intestine revealed pronounced spatial transcriptional changes with an over-representation of nutrient transporters and mucosal chemosensors of intestinal motility and secretion in anterior-medium intestine segments, whereas immunity markers are highly over-expressed in the posterior intestine segment (Calduch-Giner et al, 2016 ). This expression pattern has also been inferred for gilthead sea bream in both this and previous studies (Pérez-Sánchez et al, 2015 ; Estensoro et al, 2016 ; Simó-Mirabet et al, 2017b ) using intestinal PCR-arrays of selected markers of intestinal architecture and function. Moreover, the expression pattern of the fast-growing strain appears to be better suited to cope with enhanced feed intake and growth rates, as inferred by the up-regulated expression in the anterior intestine segment of genes involved in cell adhesion and epithelial integrity ( cdh1 and cdh17 ), mucus production ( muc2 ), Goblet cell differentiation ( hes1-b ) and FA transport ( fabp2 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This diversity is now starting to be elucidated, and microarray gene expression profiling of European sea bass intestine revealed pronounced spatial transcriptional changes with an over-representation of nutrient transporters and mucosal chemosensors of intestinal motility and secretion in anterior-medium intestine segments, whereas immunity markers are highly over-expressed in the posterior intestine segment (Calduch-Giner et al, 2016 ). This expression pattern has also been inferred for gilthead sea bream in both this and previous studies (Pérez-Sánchez et al, 2015 ; Estensoro et al, 2016 ; Simó-Mirabet et al, 2017b ) using intestinal PCR-arrays of selected markers of intestinal architecture and function. Moreover, the expression pattern of the fast-growing strain appears to be better suited to cope with enhanced feed intake and growth rates, as inferred by the up-regulated expression in the anterior intestine segment of genes involved in cell adhesion and epithelial integrity ( cdh1 and cdh17 ), mucus production ( muc2 ), Goblet cell differentiation ( hes1-b ) and FA transport ( fabp2 ).…”
Section: Discussionsupporting
confidence: 85%
“…The same relationship held true for markers of the GH/IGF axis, and we found that plasma level of IGF-I closely reflected differences in growth potentiality between fish strains, as previously observed when comparing the growth performance of gilthead sea bream with that of the stress sensitive common dentex (Bermejo-Nogales et al, 2007 ). Experimental evidence regarding the gilthead sea bream also indicates that IGF-I is highly responsive to changes in growth performance due to biotic and abiotic factors, including season and developmental stage (Mingarro et al, 2002 ; Saera-Vila et al, 2007 ), ration size (Pérez-Sánchez et al, 1995 ), crowding and handling stress (Rotllant et al, 2001 ), physical activity (Vélez et al, 2016 ), hypoxia (Martos-Sitcha et al, 2017 ) and dietary protein and lipid source (Gómez-Requeni et al, 2004 ; Benedito-Palos et al, 2007 ; Ballester-Lozano et al, 2015 ; Simó-Mirabet et al, 2017b ). Most of these changes in circulating levels of IGF-I are inversely correlated with plasma levels of GH due to the IGF-I feedback inhibition of pituitary GH synthesis and secretion (Pérez-Sánchez, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…A decreased feed intake has been observed in some fish feeding trials with diets containing MCFA (Nordrum, Olli, Rosjo, Holm, & Krogdahl, ; Williams et al, ), but not in others (Figueiredo‐Silva et al, ; Hamre et al, ; Simó‐Mirabet et al, ). An increase in dietary MCT (as 8:0 and 10:0 (50:50) up to 46% of total fat) decreased the feed intake with up to 40% in Atlantic salmon, also severely affecting growth performance (Nordrum et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…piscicida or the intestinal parasite Enteromyxum leei (Piazzon et al., ). Experimental evidence also indicates that diets enriched in dietary sodium dodecanoic acid salt enhance feed intake and growth rates in gilthead sea bream juveniles (Simó‐Mirabet et al., ), but to our knowledge, there is no information about the potential benefits of synthetic C7‐carboxylic acid salts in fish and gilthead sea bream in particular. Taking into consideration the putative impact of SCFA and MCFA supplementation reported on fish and other animal production systems, the aim of this study is to explore the potential benefits of a commercial preparation of sodium heptanoate salt in a factorial design (2 × 2) with standard or low inclusion levels of fish meal (FM) as dietary protein source.…”
Section: Introductionmentioning
confidence: 99%